Effects of hydrodynamic cavitation and temperature on nanofiltration performance for concentrating ultrafiltered skim milk. (3rd February 2023) - Mishra, Achyut; Panthi, Ram R; Beckman, Steven L; Vijayaragavan, Khrupa S; Anand, Sanjeev; Metzger, Lloyd E
Abstract : The performance of nanofiltration (NF) as influenced by hydrodynamic cavitation (HC) and filtration temperature during the concentration of milk protein concentrate (MPC) was investigated. Pasteurised skim milk was concentrated using ultrafiltration (UF) to prepare UF retentate (MPC80, 20% total solids, TS), which was then further concentrated using NF at 22°C and 50°C with or without HC treatments until permeate flux declined to 0.1 L/m 2 /h. Results showed that UF retentate can be concentrated to higher TS (up to 31.5%) at higher filtration temperature or by applying HC, with synergistic effect in combination of both treatments, during NF. Abstract : Production efficiency of milk protein concentrate can be enhanced by nanofiltration of ultrafiltered skim milk with pretreatments such as temperature elevation and hydrodynamic cavitation.